Thermal Energy Conversion in Making Biochar from Jengkok Tobacco Waste Using Pyrolysis Extrusion Model - Taufik Iskandar; Ayu Chandra Kartika Fitri (Politeknik Negeri Malang, 2022)
The pyrolysis process has many models with different characteristics and specifications. Each model provides a different conversion value depending on the temperature value, length of time, and the number of raw materials used. Jengkok Tobacco waste was dangerous because it contains Arsenic (As), and was used as a biochar product with economic and strategic value through the extrusion model pyrolysis process. The purpose of this study was to determine the thermal conversion value (yield percentage) of the pyrolysis process of tobacco waste material into biochar at the optimal temperature and processing time. The specified variables consist of process temperatures (400, 450, 500, 550, and 600°C) and processing times (30, 35, and 40 minutes). The product of the process will be analyzed statistically using the Spearman rank correlation test and followed by Minitab to produce the optimal value. The results showed that the thermal conversion value in making biochar was 29.476% (»30%) at a process temperature of 500°C and a processing time of 30 minutes.